Human-Centered Ergonomic Assesment of Concrete Block Production Workers Using OWAS Framework - Suci Ayu Lestari; Roja Safitriyawi; Tya Ulfah; Yasintha Wahida Tiana; Pesona Dessritina (Politeknik META Industri Cikarang, 2026)
Background Concrete block MSMEs rely heavily on repetitive manual material handling (MMH), forcing workers into awkward postures that increase the risk of Work-related Musculoskeletal Disorders (WMSDs). Purpose To evaluate working postures and load limits across four critical production phases and formulate feasible, low-cost ergonomic interventions. Methodology A purposive single-worker case study was conducted using the Ovako Working Posture Analysis System (OWAS) to assess biomechanical risks during mixing, transferring, molding, and drying activities. Findings The OWAS assessment classified the critical production phases into Action Categories 3 and 4, indicating significant musculoskeletal risks caused by conventional tools and non-standardized work methods. Practical ergonomic interventions, including mechanical tippers and extended press handles, were proposed to reduce these risks. Implications The findings provide a practical ergonomic improvement strategy for concrete block MSMEs. However, the single-worker design limits generalizability, highlighting the need for future longitudinal studies involving multiple workers. Originality This study bridges the gap between advanced biomechanical risk assessment and affordable field implementation by proposing practical ergonomic solutions for informal-sector concrete block production, thereby establishing a standardized baseline for future localized ergonomic research.